Eye lesion caused by adult Brugia Malayi: a first case reported in a child from Malaysia - Rohela, M.; Jamaiah, I.; Yaw, C.C. (2006)
We are reporting a case of an eye lesion caused by an adult Brugia malayi. The patient was a 3-year-old Chinese boy from Kemaman District, Terengganu, Peninsular Malaysia. He presented with a one week history of redness and palpebral swelling of his right eye. He claimed that he could see a worm in his right eye beneath the conjunctiva. He had no history of traveling overseas and the family kept dogs at home. He was referred from Kemaman Hospital to the eye clinic of Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia. On examination by the ophthalmologist, he was found to have a subconjunctival worm in his right eye. Full blood count revealed eosinophilia (10). Four worm fragments, each about 1cm long were removed from his right eye under general anesthesia. A thick blood smear stained with Giemsa was positive for microfilariae of Brugia malayi. A Brugia Rapid test done was positive. He was treated with diethylcarbamazine.